2015
DOI: 10.1080/10618562.2015.1081180
|View full text |Cite
|
Sign up to set email alerts
|

Spanwise domain effects on the evolution of the plane turbulent mixing layer

Abstract: Large Eddy Simulation is used to simulate a series of plane mixing layers. The influence of the spanwise domain on the development of the mixing layer, and the evolution of the coherent structures are considered. The mixing layers originate from laminar conditions, and an idealised inflow condition is found to produce accurate flow predictions when the spanwise computational domain extent is sufficient to avoid confinement effects. Spanwise domain confinement of the flow occurs when the ratio of spanwise domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 43 publications
(58 reference statements)
2
24
0
Order By: Relevance
“…A complete discussion of the confinement e↵ect can be found elsewhere. 36 Similar estimates of aspect ratios for the spanwise domain extent required in a shear flow have been determined in other studies. 42,43 IV.…”
Section: B Validationsupporting
confidence: 65%
See 2 more Smart Citations
“…A complete discussion of the confinement e↵ect can be found elsewhere. 36 Similar estimates of aspect ratios for the spanwise domain extent required in a shear flow have been determined in other studies. 42,43 IV.…”
Section: B Validationsupporting
confidence: 65%
“…As the flow proceeds downstream the spanwise lengthscale of the vortical structures increases, and it is important that the spanwise domain extent of the simulation does not artificially impose a maximum spanwise wavelength on the flow. In simulations of initially-laminar mixing layers with a white noise fluctuation environment, it has been observed that a local aspect ratio of L z /✓ >10 must be maintained in order to prevent the spanwise wavelength of the large scale structure being confined by the spanwise domain extent, 36 where L z is the spanwise domain extent. As this criterion is never violated in the present simulation the structures at stations 6 and 7 in Case WN are not artificially constrained by the spanwise extent, and evolve in the same manner as those found further upstream.…”
Section: Post-transition Vortical Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of secondary structure has been observed in other mixing layer simulation originating from initially-laminar conditions with a white noise disturbance environment. 27,34 Further downstream (Figures 6b-6c) a single row of 'mushroom-shaped' eruptions is visible along the span of the braid region, indicating the presence of a row of streamwise vortices. In Case WNH ( Figure 7) a similar cross-plane scalar evolution is observed, although the wavelength of the secondary instability at x = 0.07m is qualitatively much shorter than that of Case WNL.…”
Section: B Flow Visualisationmentioning
confidence: 99%
“…The spanwise domain extent is chosen such that the developing mixing layer will be free from any spanwise confinement effects. 37 The spanwise boundaries are periodic in nature. The domain is discretised into 768 × 256 × 256 cells in each direction respectively.…”
Section: Simulation Set-upmentioning
confidence: 99%